2018
DOI: 10.1038/s41598-017-19071-6
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin 1 Promotes Renal Water and Salt Reabsorption

Abstract: Caveolin-1 (Cav1) is essential for the formation of caveolae. Little is known about their functional role in the kidney. We tested the hypothesis that caveolae modulate renal salt and water reabsorption. Wild-type (WT) and Cav1-deficient (Cav1−/−) mice were studied. Cav1 expression and caveolae formation were present in vascular cells, late distal convoluted tubule and principal connecting tubule and collecting duct cells of WT but not Cav1−/− kidneys. Urinary sodium excretion was increased by 94% and urine fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Aldosterone-induced oxidation promoting cell defenestration takes place in cav-1-related autophagy [26]. In the kidney, cav-1 promotes renal water and salt reabsorption by modulating sodium-chloride cotransporter function and regulating vascular endothelial nitric oxide [4]. More in vivo studies are needed to elucidate the molecular mechanisms of striatin and cav-1 in modulating aldosterone pathways and, consequently, in regulating kidney function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aldosterone-induced oxidation promoting cell defenestration takes place in cav-1-related autophagy [26]. In the kidney, cav-1 promotes renal water and salt reabsorption by modulating sodium-chloride cotransporter function and regulating vascular endothelial nitric oxide [4]. More in vivo studies are needed to elucidate the molecular mechanisms of striatin and cav-1 in modulating aldosterone pathways and, consequently, in regulating kidney function.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, studies of striatin related to kidney function have not been reported. The cav-1 protein promotes renal water and salt reabsorption via modulation of sodium-chloride cotransporter function and regulation of vascular endothelial nitric oxide [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, both GEnC ( 45 ) and LSEC ( 46 ) fenestrations appear normal in caveolin knockout mice ( 45 ). Caveolin is expressed in GEnCs ( 47 ) but not in fenestrae ( 45 ). Caveolin interacts with mineralocorticoid receptors (MRs), and binding of aldosterone to the caveolin-MR complex induces oxidative signaling cascades ( 48 ).…”
Section: Regulation Of Fenestrationsmentioning
confidence: 99%
“…Along the same line, caveolae-mediated endocytosis has been implicated in the modulation of TRPV5 surface expression by uromodulin in HEK293 cells [107]. Evaluation of caveolin-1 and caveolae distribution in the mouse and rat kidneys showed their basolateral presence in DCT2 and principal cells (PCs) of CNT/CD but failed to confirm the apical localization of caveolae in vivo [108,109]. Apical caveolin-1 trafficking can be induced by supraphysiological doses of a vasopressin V2 receptor agonist desmopressin, as has been shown in vasopressin-deficient Brattleboro rats [110].…”
Section: Casr Function In Dctmentioning
confidence: 99%